TRANSPORTING ANTI-CANCER DRUGS THROUGH RED BLOOD CELLS - Isaqova Gavharshod Bahodir qizi; Maxarova Moxinur Baxtiyor qizi; Mirzayeva Dilshoda; Hamroxon Jur‘atova (TADQIQOTLAR, 2025)
Annotation: The use of red blood cells (RBCs) as carriers for anti-cancer drugs has emerged as a promising strategy to improve therapeutic efficacy while reducing systemic toxicity. Encapsulation or surface loading of chemotherapeutic agents within RBCs allows for controlled drug release, prolonged circulation time, and targeted delivery to tumor tissues. This approach exploits the natural biocompatibility and immune evasion properties of RBCs, potentially overcoming limitations of conventional drug delivery systems. Recent studies have demonstrated enhanced pharmacokinetics, reduced adverse effects, and improved tumor suppression using RBC-based carriers in both preclinical and early clinical settings. However, challenges remain in large-scale manufacturing, drug-loading efficiency, and ensuring safety across diverse patient populations. Continued research into engineering techniques, optimization of drug-RBC interactions, and integration with other targeted therapies could establish RBC-mediated delivery as a transformative tool in oncology.